2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8852008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Car Detection Using Unsupervised Image-to-Image Translation: From Day to Night

Abstract: Deep learning techniques have enabled the emergence of state-of-the-art models to address object detection tasks. However, these techniques are data-driven, delegating the accuracy to the training dataset which must resemble the images in the target task. The acquisition of a dataset involves annotating images, an arduous and expensive process, generally requiring time and manual effort. Thus, a challenging scenario arises when the target domain of application has no annotated dataset available, making tasks i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Arruda et al [112] Zhang et al [110] Graph reasoning Xu et al [97] Zhao et al [95] Sovinay et al [104]…”
Section: Pseudo-label Self-trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Arruda et al [112] Zhang et al [110] Graph reasoning Xu et al [97] Zhao et al [95] Sovinay et al [104]…”
Section: Pseudo-label Self-trainingmentioning
confidence: 99%
“…Furthermore, with progressive adaptation [64], they showed that applying gradient reversal at only image-level is sufficient for adaptation rather than applying both image-level and instance-level losses. Arruda et al [112] utilized the image translation module to specifically address the domain gap between daylight (source domain) and night-time (target domain) data, as shown in Fig. 20.…”
Section: Image-to-image Translationmentioning
confidence: 99%
“…In recent years, CNN-based methods are increasingly developed in the research field of vehicle detection at night. [20]- [23] used GAN-based data augmentation methods to expand the training dataset for improving the performance of the detector. Cai et al [19] combined visual saliency and prior information to generate ROIs and used CNN as a classifier.…”
Section: Related Work a Nighttime Vehicle Detectionmentioning
confidence: 99%
“…[21] and V. F. Arruda et.al. [1] proposed a generator network to further learn the feature difference between the source and target domains. These methods have achieved promising results in some specific scenes.…”
Section: Introductionmentioning
confidence: 99%